Deologiczne podziały mediów na gruncie teorii kultury dziennikarskiej Thomasa Hanitzscha (rozważania na podstawie analizy treści czasopism „Press” i „Forum dziennikarzy” z lat 2012-2016) - Olechowska, Paulina (Polityka i Społeczeństwo, 2020)
The article deals with the politicization of the media, visible in the ideological divisions among journalists, which is the consequence of the symbolic discursive strategies used by representatives of conservative-rightist and left-liberal wings. The article presents the conclusions derived from textual analysis of interviews and opinion-forming texts published in two professional periodicals Press and Forum Dziennikarzy. The main goal of the analysis is to identify and to determine the sources of the dominant narrative modes in the self-creation of the divisions in line with the epistemological theory of journalist culture authored by Thomas Hanitzsch.